Immunohistochemical Characterisation of the Whale Retina - Ruzafa, Noelia; Pereiro, Xandra; Vecino, Elena (Frontiers in Neuroanatomy, 2022)
The eye of the largest adult mammal in the world, the whale, offers a unique opportunity to study the evolution of the visual system and its adaptation to aquatic environments. However, the difficulties in obtaining cetacean samples mean these animals have been poorly studied. Thus, the aim of this study was to characterise the different neurons and glial cells in the whale retina by immunohistochemistry using a range of molecular markers. The whale retinal neurons were analysed using different antibodies, labelling retinal ganglion cells (RGCs), photoreceptors, bipolar and amacrine cells. Finally, glial cells were also labelled, including astrocytes, Müller cells and microglia. Thioflavin S was also used to label oligomers and plaques of misfolded proteins. Molecular markers were used to label the specific structures in the whale retinas, as in terrestrial mammalian retinas. However, unlike the retina of most land mammals, whale cones do not express the cone markers used. It is important to highlight the large size of whale RGCs. All the neurofilament (NF) antibodies used labelled whale RGCs, but not all RGCs were labelled by all the NF antibodies used, as it occurs in the porcine and human retina. It is also noteworthy that intrinsically photosensitive RGCs, labelled with melanopsin, form an extraordinary network in the whale retina. The M1, M2, and M3 subtypes of melanopsin positive-cells were detected. Degenerative neurite beading was observed on RGC axons and dendrites when the retina was analysed 48 h post-mortem. In addition, there was a weak Thioflavin S labelling at the edges of some RGCs in a punctuate pattern that possibly reflects an early sign of neurodegeneration. In conclusion, the whale retina differs from that of terrestrial mammals. Their monochromatic rod vision due to the evolutionary loss of cone photoreceptors and the well-developed melanopsin-positive RGC network could, in part, explain the visual perception of these mammals in the deep sea.